Drones e drone art : poder militar, ética e resistência - Rodrigues, Anna Carolina Natale (2015)
Remotely Piloted Aircrafts also known through the press as Drones, are surveillance and defense devices used by The United States of America since the Vietnam war. For a long time, this technology was in the hands of the Israeli armed forces, but in the last few years, The United States became the largest producer of this aircraft. The use of Drones became known in the last Bush administration, after the attacks of September 11, with the so-called "War on Terror". Moreover, more recently in the Obama administration with the increasing manufacture of such devices. Even though the use of this technology among civilians are increasing, the focus of this ongoing research is its use in military context, mostly American. According to Hardt and Negri (2012), nowadays there are almost two thousand armed conflicts around the world since the new millennium. These numbers keep growing, therefore, the legitimate violence, crime and terrorism became indistinguishable from one another, the terms of validation tend to collapse. The remotely piloted aircrafts can be operated thousands of miles away and often without the airspace permission of the invaded governments. We are in a time of small and intern conflicts with small enemies everywhere. Moreover, using this aircraft confirms the idea of this constant enemy, and when war is at the base of politics, the enemy has the primary function to legitimate surveillance and attacks. If the enemy is no longer concrete, understandable and traceable, then its aura is hostile, facilitating the legitimacy of that is in reality unsustainable.